Assessment of the effectiveness of Tactical Combat Casualty Care training provided to non-medical military personnel in Türkiye - Bayramoglu, Burcu; Kaplan Zamanov, Betül; Güzel Öztürk, Sinem; Kaftancı, Ismail; Tayfur, Ismail (Vojnosanitetski pregled, 2025)
Background/Aim. Tactical Combat Casualty Care (TCCC) protocols are trauma protocols used on the battlefield aimed at preventing death in the first hours of injury. In Türkiye, a regulation requires security and safety personnel to undergo TCCC training. This training is provided to non-medical military personnel (MPs) by specialized military and civilian healthcare professionals at various hospitals. The TCCC protocols include standardized interventions through protocols such as Massive hemorrhage, Airway, Respiration, Circulation, Hypothermia/Head injury (MARCH) protocol and Military Acute Concussion Evaluation (MACE) protocol to ensure consistency in trauma care. The aim of the study was to evaluate the effects of TCCC on MPs who received the training. Methods. The study included MPs who received TCCC training at Istanbul’s Sancaktepe Hospital between March 7 and May 13, 2022, and between October 3 and December 2, 2022. Volunteers who consented to participate were asked survey questions to evaluate their knowledge before and after the training on various medical conditions to assess changes in knowledge and skills. Their opinions about the training were solicited both before and after the training. In addition to the survey questions, participants were asked to provide their views and suggestions about the training through open-ended questions. Results. The study included 49 volunteers aged between 23 and 35. There was a statistically significant increase in knowledge and skill levels regarding medical conditions before and after the training (p < 0.001). Participants concluded that the training was beneficial and that the knowledge and skills acquired could be applied in the field. Conclusion. Providing TCCC training will help MPs perform life-saving interventions under fire, thereby reducing fatalities and disabilities. Additionally, TCCC training will increase health literacy awareness among civilians, enabling trained personnel to not only save lives on the battlefield but also provide first aid in civilian emergencies.